Community Participation Through The Wargaku Application Complaint Media in The City of Surabaya - Alifa, Rifda; Mustofa, Amirul; Pramudiana, Ika Devy (Universitas Muhammadiyah Sidoarjo, 2023)
The Wargaku application is one of the applications prepared by the Surabaya City Government to collect various assessments and complaints from the public directly to assess the services designed by the Surabaya City Government. Community participation in evaluating benefits and providing service complaints through the Wargaku Application will likely offer input to improve service weaknesses so that services improve quality. This research aims to analyze community participation in the implementation of the Wargaku application, which focuses on channeling community complaints. This research uses qualitative research with interactive analytical techniques. Data was collected from public complaints and Surabaya City Communication and Information Service documents. The analysis technique is carried out through condensation, data analysis and verification, and conclusions. The research shows that community participation in using the Wargaku Application still needs to be higher or as expected. Second, the government has yet to respond quickly even though the public has not used the Wargaku Application optimally. The purpose of this research is to encourage the Surabaya City Government to be more active in socializing the Wargaku Application to residents so they can make maximum use of the application.